Synergistic Effects of Compensation, Work Facilities, Skills, and Motivation on Employee Performance in Village Offices - Nia Hidayana; Ellin Herlina; Deviari Damalita (International Journal of Management, Economic, Business and Accounting, 2025)
Purpose of the study — This research aims to find out: How big is the influence of Compensation, Work Facilities, Skills and Motivation on the Performance of Village Office Employees in Suranenggala District, Cirebon Regency, both partially and simultaneously. Research Place at Village Offices in Suranenggala District, Cirebon Regency. Research method— The population in this study was 111 Village Office Employees in Suranenggala District, Cirebon Regency, a sample of 53 people. The research design uses a quantitative approach, survey method, with data analysis techniques using Multiple Linear Regression analysis. Result— The results of this research show: 1) There is a significant positive influence of partial compensation on the performance of Village Office employees in Suranenggala District, Cirebon Regency, 22%, the remaining 78% is influenced by other factors. 2) There is a significant positive influence of partial work facilities on the performance of Village Office employees in Suranenggala District, Cirebon Regency, amounting to 22.6%, the remaining 77.4% is influenced by other factors. 3) There is a significant positive influence of skills partially on the performance of Village Office employees in Suranenggala District, Cirebon Regency, amounting to 68.8%, the remaining 31.2% is influenced by other factors. 4) There is a significant positive influence of partial motivation on the performance of Village Office employees in Suranenggala District, Cirebon Regency, amounting to 31%, the remaining 69% is influenced by other factors. 5) There is a significant positive influence of compensation, work facilities, skills and motivation simultaneously on the performance of Village Office employees in Suranenggala District, Cirebon Regency, amounting to 99.9%. The remaining 1% is influenced by other factors. Conclusion— Overall, compensation, work facilities, skills, and motivation are interrelated and collectively contribute to employee performance. Effective management needs to consider all these factors to create a productive work environment and motivate employees to give their best.